Influence of digital educational platforms on cognitive development and emotional well-being - Vladimir Beketov; Marina Taranova; Marina Lebedeva (Institute of Advanced Engineering and Science, 2026)
This study aimed to identify psychophysiological markers that shape students’ cognitive–emotional trajectories during learning with Moodle 3.9, supplemented by Canvas learning management system (LMS) for video delivery and Kahoot for game-based assessments. The experiment involved 124 undergraduate students and spanned 16 weeks with five measurement points: the experimental group studied using digital platforms, while the control group followed a traditional format. The methodology incorporated Raven’s, Stroop, and N-back cognitive tests; measurements of heart rate, skin conductance, and cortisol levels; facial expression analysis; and learning-platform data. Working memory improved by 2.2 points with an effect size of d=2.14, and Stroop interference decreased by 36 milliseconds. The physiological cost included a reduction in heart-rate variability (root mean square of successive differences or RMSSD) from 42±12 to 28±8 ms and a two-hour shift in daily cortisol rhythms. Cluster analysis revealed three behavioral profiles. The strategic group scored 8.7 out of 10 while completing 40% of the material. Predictive models identified academic failure with 82.3% accuracy 21 days in advance, showing 76% sensitivity and 81% specificity. Individualized interventions triggered by physiological indicators increased academic performance by 24% and reduced stress by 38%. The return on investment was 4.2 to 1. The findings support the integration of early-warning algorithms into educational systems.